The scientific diaspora as a strategic instrument of scientific diplomacy in Latin America - Santos Blas, Gena Meylin (2026)
This study analyzes the importance of the scientific diaspora as a strategic resource for promoting science diplomacy in Latin American countries. Based on a conceptual and comparative review of the policies and initiatives implemented by these countries, the document examines how engaging scientists living abroad can contribute to strengthening national capacities in science, technology, and innovation (STI). Therefore, the analysis specifies how the strategic mobilization of the scientific diaspora makes it possible to expand international knowledge networks, facilitate access to scientific and technological cooperation, and strengthen STI governance by incorporating highly qualified human capital in the development of innovation projects. In addition, the study highlights how the participation of these scientific communities abroad contributes to the positioning of countries by strengthening their soft power through scientific diplomacy.